New Mode for the On-Line Determination of Amiloride in Pure and Pharmaceutical Preparation Using CFIA Via the Use of Linear Array from Six LED (Snow White) with One Solar Cell in a Homemade Ayah 6Sx1-T-1D Solar CFI Analyser - M.A. Shakir, Issam (Iraqi Journal of Science, 2023)
A newly flow injection-turbidimetric method characterized by it is speed and sensitivity has been developed for the determination of Amiloride in pure and pharmaceutical preparations. It is based on the formation of yellowish white precipitate for the Amiloride-phosphomolybidic acid ion pair in aqueous medium. Turbidity was measured by Ayah 6Sx1-T-1D solar cell CFI analyser via the attenuation of incident light from the surfaces precipitated particles at 0-180. The Chemical and physical parameters were investigated. Linear dynamic range for the attenuation of incident light versus Amiloride concentration was of 0.005-10 mmol.L-1, with the correlation coefficient (r) of 0.9986 , while the percentage linearity (r2%) was 99.71%. The L.O.Q was of 23.14 μg/sample, while L.O.D (S/N=3) =5.74 ng/sample from the stepwise dilution for the minimum concentration in the calibration graph. The R.S.D% at 3, 9 mmol.L-1 Amiloride is less than 0.5% (eight replicates) using 50 μL sample volume. Through put was of 40 sample.hr-1. The method was applied successfully for the determination of Amiloride in pharmaceutical preparations. A comparison was made using the standard additions method via the use paired t-test. It showed that there was no significant difference between the quoted value of each individual paired t-test with calculated t-value at 95% confidence interval from developed method. In addition to comparison between two methods and calculate t-value, it was noticed that there was no significant difference between the two methods at =0.05 (95% confidence level).